Awe/Gratitude as an Experiential Aspect of Spirituality and Its Association to Perceived Positive Changes During the COVID-19 Pandemic - Büssing, Arndt; Rodrigues Recchia, Daniela; Dienberg, Thomas; Surzykiewicz, Janusz; Baumann, Klaus (Frontiers in Psychiatry, 2021)
Background: While the COVID-19 pandemic has affected the lives of almost all people worldwide, many people observed also positive changes in their attitudes and behaviors. This can be seen in the context of posttraumatic growth. These perceived changes refer to five main categories: Nature/Silence/Contemplation, Spirituality, Relationships, Reflection on life, and Digital media usage. A previous study with persons recruited in June 2020 directly after the lockdown in Germany showed that the best predictors of these perceived changes related to the Corona pandemic were the ability to mindfully stop and pause in distinct situations, to be “spellbound at the moment” and to become “quiet and devout,” indicating moments of wondering awe, with subsequent feelings of gratitude. Now, we intended to analyze (1) by whom and how strongly awe/gratitude was experienced during the COVID-19 pandemic, and (2) how these feelings relate to perceived changes and experienced burden, and (3) whether or not feelings of awe/gratitude contribute to participants' well-being or may buffer perceived burden in terms of a resilience factor. Methods: Online survey with standardized questionnaires [i.e., WHO-Five Well-being Index (WHO5), Life satisfaction (BMLSS), Awe/Gratitude scale (GrAw-7), and Perceived Changes Questionnaire (PCQ)] among 2,573 participants (68% women; mean age 48.7 ± 14.2 years, 74% with a Christian affiliation) from Germany recruited between June and November 2020. Results: Awe/Gratitude scored significantly higher particularly among women (Cohen's d = 0.40), older persons (d = 0.88), persons who rely on their faith as a “stronghold in difficult times” (d = 0.99), those with higher well-being (d = 0.70), and lower perceptions of loneliness (d = 0.49). With respect to perceived changes during the pandemic, more intense feelings of Awe/Gratitude were particularly related to Nature/Silence/Contemplation (r = 0.41), Spirituality (r = 0.41), and Relationships (r = 0.33). Regression analyses revealed that the best predictors of Awe/Gratitude (R2 = 0.40) were the frequency of meditation, female gender, life satisfaction and well-being, faith as a stronghold, and perceived burden and also life reflection, while Nature/Silence/Contemplation and Relationships had a further, but weaker, impact on Awe/Gratitude as a dependent variable. Awe/Gratitude was moderately associated with well-being (r = 0.32) and would predict 9% of participants' well-being variance. The best predictors of participants' well-being were multidimensional life satisfaction and low perceived burden (related to the pandemic), and further Awe/Gratitude and Nature/Silence/Contemplation; these would explain 47% of variance in well-being scores. However, Awe/Gratitude cannot be regarded as a buffer of the negative aspects of the COVID-19 pandemic, as it is only marginally (though negatively) related to perceived burden (r = −0.15). Mediation analysis showed that Awe/Gratitude mediates 42% of the link between well-being as a predictor on Nature/Silence/Contemplation as an outcome and has a direct effect of β = 0.15 (p < 0.001) and an indirect effect of β = 0.11 (p < 0.001). Further, Awe/Gratitude mediates 38% (p < 0.001) of the link between Nature/Silence/Contemplation as a predictor on well-being as the outcome; the direct effect is β = 0.18 (p < 0.001), and the indirect effect is β = 0.11 (p < 0.001). Conclusions: The general ability to experience Awe/Gratitude particularly during the COVID-19 pandemic may sensitize to perceive the world around (including nature and concrete persons) more intensely, probably in terms of, or similar to, posttraumatic growth. As this awareness toward specific moments and situations that deeply “touch” a person was higher in persons with more intense meditation or prayer practice, one may assume that these practices may facilitate these perceptions in terms of a training. However, the experience of Awe/Gratitude does not necessarily buffer against adverse events in life and cannot prevent perceived burden due to the corona pandemic, but it facilitates to, nevertheless, perceive positive aspects of life even within difficult times. As Awe/Gratitude is further mediating the effects of Nature/Silence/Contemplation on well-being, intervention programs could help to train these perceptions, as these self-transcendent feelings are also related to prosocial behaviors with respectful treatment of others and commitment to persons in needs, and well-being.